Investigating teachers' implementation and strategies on higher order thinking skills in school based assessment instruments / Diana Marie Wilson and Suthagar Narasuman - Wilson, Diana Marie; Narasuman, Suthagar (Universiti Teknologi MARA, 2020)
Higher Order Thinking Skills (HOTS) among students is crucial to be developed in the education system as to prepare students to face the 21st century situations as well as to develop students to reach their full potential. In Malaysia, the integration of HOTS in the new School Based Assessment is a move towards realizing the government's aspiration of achieving a quality education system. The study seeks to investigate teachers' challenges and their strategies on integrating Higher Order Thinking Skills (HOTS) in School Based Assessment (SBA). This study was conducted at three Secondary schools in Tawau, Sabah, Malaysia. This study has been conducted using the descriptive quantitative research design. The instrument used is questionnaire and 68 teachers who are teaching Form One, Form Two and Form Three students at the schools participated in this study. Data is analysed using descriptive statistic and frequency, percentage, mean and standard deviation are analysed by using SPSS package (version 22). The results of the finding outlined several challenges faced by the respondents during the integration of HOTS in SBA instruments. The findings in this study also highlight the strategies employed by teachers to integrate HOTS in SBA.